“The Right to Live in the City”: Exploring Discrimination Against the Urban Poor Inhabitants of Ubon Ratchathani, North-Eastern Thailand - Sumnuanyen, Kingkarn; Promphakping, Buapun (The journal of contemporary issues in business and government, 2021)
The purpose of this paper is to explore the concept of achieving the “right to live in the city” for poor urban inhabitants in north-eastern Thailand. We raise the question of who has the right to set the rules of urban spaces, which have changed significantly in terms of the spatial exclusion of poor people. Our study adopts a qualitative case study, using a purposive sampling technique. Interviews were conducted with 30 key informants between August and October 2018. Data were coded, analysed and interpreted. Our findings show that the poor not only have restricted rights to physical space, but the inhabitants are prevented from having the right to live on their own land. We examine the context of new forms of “right to live in the city” associated with the right to historical identity, the right to equal distribution of resources, the right to equal access to resources, and the right to housing inheritance.